2019
DOI: 10.1111/bph.14770
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin exerts anti‐colorectal cancer activity by targeting the β‐catenin/T‐cell factor complex

Abstract: Background and Purpose Salinomycin is a well‐known inhibitor of human cancer stem cells ( CSCs ). However, the molecular mechanism(s) by which salinomycin targets colorectal CSCs is poorly understood. Here, we have investigated underlying antitumour mechanisms of salinomycin in colorectal cancer cells and three tumour models. Experimental Approach The inhibitory effect of salinomycin on the Wnt/β‐catenin pathway was analysed with the SuperTopF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 62 publications
(83 reference statements)
0
23
0
1
Order By: Relevance
“…5b and c ). Since the miR-194 target genes, TCF7L2 and Foxa1 , were proved to be involved in the regulation of cell growth 27 , 28 , we speculated that miR-194 may play a role in PA-induced cytotoxicity via regulating TCF7L2 and Foxa1. Notably, the interference of miR-194 reversed the inhibitory effect of PA on cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5b and c ). Since the miR-194 target genes, TCF7L2 and Foxa1 , were proved to be involved in the regulation of cell growth 27 , 28 , we speculated that miR-194 may play a role in PA-induced cytotoxicity via regulating TCF7L2 and Foxa1. Notably, the interference of miR-194 reversed the inhibitory effect of PA on cell viability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described 38 . Briefly, cells grown on coverslips or the sectioned organoids (7 μm) were fixed with 4% paraformaldehyde and permeabilized with 0.4% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were diagnosed with CRC by endoscopic biopsies and subsequently confirmed by histology in the First Affiliated Hospital of Shenzhen University. Establishment of PDTXs was performed as previous described 38 , 40 . Briefly, necrotic and supporting tissues of patient's tumor were removed and about 20-30 mg of tumor fragments were subcutaneously (s.c.) implanted into the right flank of 8-week-old male NPG mice using a trocar.…”
Section: Methodsmentioning
confidence: 99%
“…It was revealed that Metformin could reduce tumorigenesis by inhibiting mitochondrial complex I [ 133 ]. Cancer therapy benefits from some antibiotics, which have been proven to inhibit the respiratory function of mitochondria; for example, salinomycin showed anti-tumor activity in colorectal cancer [ 134 ], and it was also indicated that mitochondrial function could be disrupted by salinomycin [ 135 , 136 ]. ROS are produced in the electron transport chain(ETC) during cell energy metabolism, as found in previous studies, a lower ROS level was observed to maintain CSC properties in CSC niche, thus, eliminating CSCs via a ROS inducer was proposed.…”
Section: Targeted Strategies Of Cscsmentioning
confidence: 99%